IMPLEMENTASI PERPUSTAKAAN SEKOLAH SEBAGAI SUMBER BELAJAR DALAM MENINGKATKAN PRESTASI BELAJAR SISWA - Kamulyan, Mulyadi Sri; Primasari, Febriana (Profesi Pendidikan Dasar, 2014)
The utilization existence of the library as a resource center for students in elementaryschool is a necessity that needs to be examined. Although the school does not have thepersonnel in charge of taking care of a special library, but it can be handled by a designatedteacher under the control of the principal to optimize he library utilization. Theeffectiveness of implementation will have an impact on the growth of like reading in theschool library for students on one hand also creativity of teachers in using library as alearning resource for certain theme, so that students want to come or use to the schoollibrary. There is a prediction that the utilization of school library is able to increase thestudent achievement.Â